The effects of climate change on respiratory allergy and asthma induced by pollen and mold allergens - D’Amato, Gennaro; Chong‐Neto, Herberto Jose; Monge Ortega, Olga Patricia; Vitale, Carolina; Ansotegui, Ignacio; Rosario, Nelson; Haahtela, Tari; Galan, Carmen; Pawankar, Ruby; Murrieta‐Aguttes, Margarita; Cecchi, Lorenzo; Bergmann, Christian; et al. (Allergy (Copenhagen), 2020)
The impact of climate change on the environment, biosphere, and biodiversity has become more evident in the recent years. Human activities have increased atmospheric concentrations of carbon dioxide (CO2) and other greenhouse gases. Change in climate and the correlated global warming affects the quantity, intensity, and frequency of precipitation type as well as the frequency of extreme events such as heat waves, droughts, thunderstorms, floods, and hurricanes. Respiratory health can be particularly affected by climate change, which contributes to the development of allergic respiratory diseases and asthma. Pollen and mold allergens are able to trigger the release of pro‐inflammatory and immunomodulatory mediators that accelerate the onset the IgE‐mediated sensitization and of allergy. Allergy to pollen and pollen season at its beginning, in duration and intensity are altered by climate change. Studies showed that plants exhibit enhanced photosynthesis and reproductive effects and produce more pollen as a response to high atmospheric levels of carbon dioxide (CO2). Mold proliferation is increased by floods and rainy storms are responsible for severe asthma. Pollen and mold allergy is generally used to evaluate the interrelation between air pollution and allergic respiratory diseases, such as rhinitis and asthma. Thunderstorms during pollen seasons can cause exacerbation of respiratory allergy and asthma in patients with hay fever. A similar phenomenon is observed for molds. Measures to reduce greenhouse gas emissions can have positive health benefits.